THU0349 Methotrexate reduces adalimumab immunogenicity in patients with spondyloarthritis: a randomized clinical trial. (15th June 2017) - Ducourau, E; Rispens, T; Dernis, E; Guilchard, F Le; Andras, L; Perdriger, A; Lespessailles, E; Martin, A; Cormier, G; Armingeat, T; Devauchelle-Pensec, V; Solau-Gervais, E; et al.
Abstract : Background: TNF inhibitors are effective in treating spondyloarthritis (SpA). However, anti-drug antibodies (ADA) may be responsible for decreased efficacy. Methotrexate reduces adalimumab immunogenicity in rheumatoid arthritis (1). Objectives: The aim of the study was to evaluate the effect of methotrexate on ADA detection in SpA patients receiving adalimumab. Methods: One hundred and ten SpA patients eligible for adalimumab 40 mg S/C eow were randomized on a 1:1 ratio to receive MTX 10 mg s/c every week, 2 weeks prior (V0) adalimumab (MTX+), or adalimumab alone (MTX-). ADA detection and adalimumab concentration were assessed 4 weeks (V2), 8 weeks (V3), 12 weeks (V4) and 26 weeks (V5) after starting adalimumab (V1). The main outcome was the percentage of positive patients for ADA detection at V5 or last available visit. Results: Patients' characteristics (sex, previous TNF inhibitors, disease duration, HLA B27 +/-, BMI) were comparable between the two groups. One hundred and seven patients were analyzed, 55 in the MTX+ group versus 52 in the MTX- group. ADA were detected at V5, in 39/107 (36.4%) patients; 13/52 (25%) in the MTX+ group versus 26/55 (47.3%) in the MTX- group (p=0.03). Adalimumab concentrations were statistically higher in the MTX+ group as compared with the MTX- group at V2, V3, V4 and V5 (Figure 1 ). There was no difference in terms of adverse events and efficacy between the two groups. Conclusions: MTX reduces immunogenicity and ameliorates pharmacokinetics of adalimumab in SpA patients. The clinical impact of this combination requires longer period studies. References: Krieckaert CL, Nurmohamed MT, Wolbink GJ. Ann Rheum Dis 2012. Acknowledgements: The authors thank Bruno Giraudeau for his methodological advice in the study design; Yoann Desvignes for technical support with the study protocol; Elody Marnat for data management; Coraline Gadras and Céline Vignault for blood sample management; Anne-Claire Duveau for technical assistance. This work was promoted by the Regional University Hospital Center of Tours and supported by grants from the French Ministry for Health and Sport within the framework of the "Programme Hospitalier de Recherche Clinique 2011" and received fundings from the "Lions Club, Tours Val de France" and from Nordic Pharma who provided subcutaneous methotrexate. This work was a collaborative venture by HUGO (Hôpitaux Universitaires du Grand Ouest – Western France University Hospitals Network). Disclosure of Interest: E. Ducourau: None declared, T. Rispens: None declared, E. Dernis: None declared, F. Le Guilchard: None declared, L. Andras: None declared, A. Perdriger: None declared, E. Lespessailles Grant/research support from: MSD, Novartis, UCB, Pfizer, Consultant for: MSD, Novartis, UCB, Pfizer, A. Martin: None declared, G. Cormier: None declared, T. Armingeat: None declared, V. Devauchelle-Pensec: None declared, E. Solau-Gervais: None declared, B. Le Goff: None declared, A. de Vries: None declared, E. Piver: None declared, D. Ternant Consultant for: Sanofi, Amgen, P. Goupille Consultant for: Abbvie, Biogaran, BMS, Hospira, Janssen, MSD, Pfizer, Sanofi-Genzyme, UCB, D. Mulleman Grant/research support from: Nordic Pharma, Abbvie, Consultant for: MSD, Novartis, UCB, Pfizer